Antioxidant and ACE Inhibitory Bioactive Peptides Purified from Egg Yolk Proteins - Marwa Yousr (International Journal of Molecular Sciences, 2015)
Protein by-products from the extraction of lecithin from egg yolk can be converted into value-added products, such as bioactive hydrolysates and peptides that have potential health enhancing antioxidant, and antihypertensive properties. In this study, the antioxidant and angiotensin converting enzyme (ACE) inhibitory activities of peptides isolated and purified from egg yolk protein were investigated. Defatted egg yolk was hydrolyzed using pepsin and pancreatin and sequentially fractionated by ultrafiltration, followed by gel filtration to produce egg yolk gel filtration fractions (EYGF). Of these, two fractions, EYGF-23 and EYGF-33, effectively inhibited the peroxides and thiobarbituric acid reactive substance (TBARS) in an oxidizing linoleic acid model system. The antioxidant mechanism involved superoxide anion and hydroxyl radicals scavenging and ferrous chelation. The presence of hydrophobic amino acids such as tyrosine (Y) and tryptophan (W), in sequences identified by LC-MS as WYGPD (EYGF-23) and KLSDW (EYGF-33), contributed to the antioxidant activity and were not significantly different from the synthetic BHA antioxidant. A third fraction (EYGF-56) was also purified from egg yolk protein by gel filtration and exhibited high ACE inhibitory activity (69%) and IC50 value (3.35 mg/mL). The SDNRNQGY peptide (10 mg/mL) had ACE inhibitory activity, which was not significantly different from that of the positive control captopril (0.5 mg/mL). In addition, YPSPV in (EYGF-33) (10 mg/mL) had higher ACE inhibitory activity compared with captopril. These findings indicated a substantial potential for producing valuable peptides with antioxidant and ACE inhibitory activity from egg yolk.